Estimating the effects of COVID-19 on essential health services utilization in Uganda and Bangladesh using data from routine health information systems - Angeles, Gustavo; Silverstein, Hannah; Ahsan, Karar Zunaid; Kibria, Mohammad Golam; Rakib, Nibras Ar; Escudero, Gabriela; Singh, Kavita; Mpiima, Jamiru; Simmons, Elizabeth; Weiss, William (Frontiers in Public Health, 2023)
Background: Since March 2020, the coronavirus disease 2019 (COVID-19) pandemic has been a major shock to health systems across the world. We examined national usage patterns for selected basic, essential health services, before and during the COVID-19 pandemic in Uganda and Bangladesh, to determine whether COVID-19 affected reporting of service utilization and the use of health services in each country.Methods: We used routine health information system data since January 2017 to analyze reporting and service utilization patterns for a variety of health services. Using time series models to replicate pre-COVID-19 trajectories over time we estimated what levels would have been observed if COVID-19 had not occurred during the pandemic months, starting in March 2020. The difference between the observed and predicted levels is the COVID-19 effect on health services.